The Lost World - Doyle, Arthur Conan; Series Editor Blower, Bill and Parminter, Sue (Oxford Oxford University Press, 2014)
You said that you wanted danger, didn't you?' says McArdle, the editor of the Daily Gazette. And he sends his young reporter, Malone, on a strange journey into South America with the famous Professor Challenger. Challenger believes he can find a lost world full of dinosaurs in the middle of the Amazon forest. But this world is dangerous to reach, and, once the Professor and his small group of explorers arrive, things get even more dangerous for them. Will they return alive?--P. [4] of cover.
Include Illustration
Keywords: South America -- Challenger, Professor (Fictitious character) -- Dinosaurs